RC circuit:
When the input to the system represented by the term on the right-hand
side of the DE is non-zero, the DE can be solved to find its particular
or steady state solution. We first a constant input:
![$\displaystyle \tau\dot{v}_C(t)+v_C(t)=v_s(t)=V_s$](img278.svg) |
(84) |
With a constant input, the particular solution
must be constant
as well, and the DE becomes
, i.e., the solution is trivially
![$\displaystyle v_C(t)=V_s$](img281.svg) |
(85) |
We next consider a sinusoidal input
. We first assume
the input is a complex exponential input:
![$\displaystyle \tau\dot{v}_C(t)+v_C(t)=v_s(t)=e^{j\omega t}=\cos(\omega t)+j\sin(\omega t)$](img283.svg) |
(86) |
and assume
![$\displaystyle v_C(t)=A\;e^{j\omega t},\;\;\;\;\;\frac{d}{dt}v_C(t)=j\omega A\;e^{j\omega t}$](img284.svg) |
(87) |
and substitute them back into the DE to get
![$\displaystyle j\omega \tau A e^{j\omega t}+A e^{j\omega t}
=(j\omega \tau+1)A\; e^{j\omega t}=e^{j\omega t}$](img285.svg) |
(88) |
Solving for
we ge
where![$\displaystyle \;\;\;\;\;\;\vert A\vert=\frac{1}{\sqrt{\omega^2 \tau^2+1}},\;\;\;\;\;
\phi=\angle A=\tan^{-1}\omega\tau$](img287.svg) |
(89) |
and the solution is:
![$\displaystyle A\;e^{j\omega t}=\frac{1}{\sqrt{\omega^2 \tau^2+1}} e^{j(\omega t-\phi)}$](img288.svg) |
(90) |
As the system is linear therefore superposition applies, we
can find the output corrresponding to a sinusoidal input
, by taking the real part
of the solution above:
![$\displaystyle v_C(t)=Re\left[\frac{1}{\sqrt{\omega^2 \tau^2+1}} e^{j(\omega t-\phi)}\right]
=\frac{1}{\sqrt{\omega^2 \tau^2+1}} \cos(\omega t-\phi)$](img290.svg) |
(91) |
Alternatively, this RC circuit can also be solved more conveniently by
the phasor method, if only the steady state solution (the particular
solution) is of interest. The phasor of the input voltage
is simply 1, and the phasor of the voltage across
can be found by voltage divider:
![$\displaystyle V_C=V\frac{Z_C}{Z_R+Z_C}=\frac{1/j\omega C}{R+1/j\omega C}
=\frac...
...ga RC+1}=\frac{1}{j\omega \tau+1}
=\frac{1}{\sqrt{\omega^2\tau^2+1}} e^{-j\phi}$](img292.svg) |
(92) |
where
. Converting this phasor to time
function we get
![$\displaystyle v_C(t)=Re[V_Ce^{j\omega t}]
=Re\left[\frac{1}{\sqrt{\omega^2\tau^...
...{j(\omega t-\phi)}\right]
=\frac{1}{\sqrt{\omega^2\tau^2+1}}\cos(\omega t-\phi)$](img294.svg) |
(93) |